On the Elasticities of Harvesting Rules - Fwu-Ranq Chang (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper, we rank the relative importance of the exogenous parameters upon the optimal harvesting size in a stochastic rotation problem. We show that when the tree growth follows geometric Brownian motion, the harvesting size is most elastic to the harvesting cost, followed by the interest rate, and is least elastic to the parameters of tree growth. Similar ranking holds for the linear growth case. In both cases the harvesting size is increasing and concave in the harvesting cost, bounded between two parallel lines. The harvesting decision is made according to a stochastic extension of the Faustmann formula.
Keywords: 330; stochastic rotation problem; the Faustmann formula; site value; homogeneity conditions; and seedling value